A Phytophthora palmivora Extracellular Cystatin-Like Protease Inhibitor Targets Papain to Contribute to Virulence on Papaya - Gumtow, Rebecca; Wu, Dongliang; Uchida, Janice; Tian, Miaoying (Molecular plant-microbe interactions, 2018)
Papaya fruits, stems, and leaves are rich in papain, a cysteine protease that has been shown to mediate plant defense against pathogens and insects. Yet the oomycete Phytophthora palmivora is a destructive pathogen that infects all parts of papaya plants, suggesting that it has evolved cysteine protease inhibitors to inhibit papain to enable successful infection. Out of five putative extracellular cystatin-like cysteine protease inhibitors (PpalEPICs) from P. palmivora transcriptomic sequence data, PpalEPIC8 appeared to be unique to P. palmivora and was highly induced during infection of papaya. Purified recombinant PpalEPIC8 strongly inhibited papain enzyme activity, suggesting that it is a functional cysteine protease inhibitor. Homozygous PpalEPIC8 mutants were generated using CRISPR/Cas9-mediated gene editing via Agrobacterium-mediated transformation (AMT). Increased papain sensitivity of in-vitro growth and reduced pathogenicity during infection of papaya fruits were observed for the mutants compared with the wild-type strain, suggesting that PpalEPIC8, indeed, plays a role in P. palmivora virulence by inhibiting papain. This study provided genetic evidence demonstrating that plant-pathogenic oomycetes secrete cystatins as important weapons to invade plants. It also established an effective gene-editing system for P. palmivora by the combined use of CRISPR/Cas9 and AMT, which is expected to be applicable to other oomycetes.